Tax-Optimal Step-Up and Imperfect Loss Offset - Markus Diller (BuR - Business Research, 2012)
In the field of mergers and acquisitions, German and international tax law allow for several opportunities to step up a firm's assets, i.e., to revaluate the assets at fair market values. When a step-up is performed the taxpayer recognizes a taxable gain, but also obtains tax benefits in the form of higher future depreciation allowances associated with stepping up the tax base of the assets. This tax-planning problem is well known in taxation literature and can also be applied to firm valuation in the presence of taxation. However, the known models usually assume a perfect loss offset. If this assumption is abandoned, the depreciation allowances may lose value as they become tax effective at a later point in time, or even never if there are not enough cash flows to be offset against. This aspect is especiallyrelevant if future cash flows are assumed to be uncertain. This paper shows that a step-up may be disadvantageous or a firm overvalued if these aspects are not integrated into the basic calculus. Compared to the standard approach, assets should be stepped up only in a few cases and - under specific conditions - at a later point in time. Firm values may be considerably lower under imperfect loss offset.
urn:nbn:de:0009-20-33088
Keywords: 650; CAPM; business taxation; hidden reserves; step-up; Steuervergünstigung; Verlust; Unternehmenswert; Übernahme; Cash Flow; Betriebliche Investitionstheorie; Deutschland; Welt